(untitled) (Research, Society and Development, 2022)
This article aims to identify the complications presented in patients with COVID-19 during their stay in intensive care. We conducted a retrospective documentary cohort study in medical records of adults admitted to an Intensive Care Unit designated for the treatment of COVID-19 patients, from September 2020 to January 2021. The sample consisted of 47 medical records of patients over 18 years old, with confirmed diagnosis for SARS-COV-219 by reverse transcription test and polymerase chain reaction. Medical records of 24 women (51,1%) and 23 men (49,9%) were included in the study, with an average of 70 years old. The main complications described involved the blood, immune and respiratory systems. Electrolyte disorder was the most frequent complication observed in 100% of the patients, followed by leukocytosis (95,7%), acid-base disorder and acute respiratory failure, present in 87,2% of the analysed cases. We conclude that COVID-19 causes damage to multiple systems, directly affecting the prognosis of patients.